Characterization of the Main Character in the Film "Enola Holmes": Through Erik Erikson's Theory (Social Development Theory) - Arya Muharsyah, Shafa; Anggraini, Dwi; Fitriyah, Fitriyah (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study analyzes the characterization of Enola Holmes, the main character in the 2020 film Enola Holmes, through Erik Erikson's psychosocial development theory. Both literature and film provide valuable insights into personal psychology and societal challenges. Erikson's stages—Identity vs. Role Confusion, Autonomy vs. Shame and Doubt, Initiative vs. Guilt, and Trust vs. Mistrust—are well illustrated in Enola's character development. Using qualitative descriptive methods, this study examines conversations and scenarios that highlight Enola's growth and independence, influenced by her relationship with her mother and the social norms of Victorian England. The analysis demonstrates how Erikson's psychosocial theory, which sheds light on identity development within a patriarchal cultural context, aligns with Enola's journey of self-discovery and resilience. The findings reveal that Enola's journey is marked by a strong sense of independence, exploration of identity, and resistance to societal expectations, underscoring the principles that individuals hold dear. This analysis, grounded in Erik Erikson's theory, provides insights into individual development as it relates to the character of Enola Holmes in the film.